Radar Altimeter Echo-Signal Analytical Model - D. S. Borovitsky; A. E. Zhesterev; V. P. Ipatov; R. M. Mamchur (Известия высших учебных заведений России: Радиоэлектроника, 2017)
To design and analyze signal processing procedures in the onboard receiver of a space-based altimeter an analytical echo-signal model is desirable which combines compactness with acceptable accuracy of presenting average return power dependency on the measured parameters. On the same premises as for the popular Brown’s model and for the scenario of a sharp antenna beam the expression is proposed linking the mean return power profile to parameters to be measured: orbit altitude, significant wave height and antenna boresight angle. Only the “ready” functions enter the equation obtained, so that no numerical integration is necessary. The model proposed is feasible to optimize echo-signal search and tracking algorithms as well as to evaluate the potential accuracy of joint estimate of the abovementioned parameters.